Integrated Arrays of Micro Resistance Temperature Detectors for Monitoring of the Short-Circuit Point in Lithium Metal Batteries - Lianqi Zhao; Cong Wu; Xinshui Zhang; Yue Zhang; Chao Zhang; Lei Dong; Longxing Su; Jin Xie (Batteries, 2022)
Short-circuit induced thermal runaway is one of the main obstacles that hinder the large-scale commercial applications of lithium metal batteries. The fast and accurate detection of an internal short-circuit is, therefore, a key step for preventing thermal runaway. The traditional temperature detection is mainly to place temperature sensors outside the battery, which is far from the actual hotspot inside the cell and has a lag in response. In this study, we integrated arrays of micro resistance temperature detectors (AMRTDs) inside the pouch cell. AMRTDs can be used for the detection of a short-circuit with a high temporal and spatial resolution. We show that the initial short-circuit may induce a high temperature local hotspot exceeding 300 °C, whereas the nearby area was still maintained at near room temperature. Our work provides a design strategy for in-situ detection of short-circuits in lithium metal batteries.